(untitled) (The Research of Medical Science Review, 2025)
Objective: To evaluate the effectiveness of blood transfusion protocol among the post-coronary artery bypass graft (CABG) surgery patients in intensive care unit (ICU) in order to improve blood transfusion safety.Methods: The audit was done retrospectively in the cardiac surgery ICU of Sheikh Mohamed Bin Zayed Al Nahyan Institute of Cardiology, Quetta (SMBZAN ICQ) Baluchistan. All CABG patients’ who received blood transfusions postoperatively in the surgical ICU from 1st July 2023 to 1st January 2024 were included and the National Blood Authority’s (NBA) audit tool was modified for data collection.Results: It was found that 54% of patients underwent packed cell volume (PCV) transfusion during this period. Among these; the transfusion rate was 64% for men and 36% for women. 93% of transfusions were based on clinical symptoms including respiratory and hemodynamic instability. Furthermore, 7% of transfusions based solely on low haemoglobin levels, were considered inappropriate because there was no evidence of respiratory or hemodynamic decompensation in the health record.Conclusion: The audit signifies positively impacted PCV transfusion appropriateness in post CABG patients, both in terms of quality and quantity.